Utilization of Biogas Slurry Doses from Goat Faeces with MOL (Micro Local Organisms) Banana Stem on Turi Productivity (Sesbania grandiflora) in Samosir Regency - Simson Sianturi; Nurzainah Ginting; Sayed Umar; Nevy Diana Hanafi; Yunilas . (Jurnal Peternakan Integratif, 2019)
This study aims to investigate the effect of  utilization of biogas slurry doses with MOL (Micro Local Organisms) Banana Stumps on Turi Productivity (Sesbania grandiflora). This research was conducted in Samosir Regency, North Sumatra starting from May to September  2018. The design used in this study was a completely randomized design with 4 treatment levels of 5 replications, the data analysis used was Duncan's Advanced Test. Treatment with various doses of biogas slurry fertilizer by input of goat faeces which is fermented with MOL (Micro Local Organism), 2 liter MOL banana stem. P0 = 0, P1 = 20, P2 = 40, P3 = 60 (t / h / yr). The variables observed were plant height, stem diameter, number of stems, number of leaves, and leaf width. The results of the study showed that the fermentation of goat's bio-gas slurry fertilizer with various doses of fertilizing gave a significant influence on the parameters of the study, namely plant height, number of stems, number of leaves, and stem diameter. The best response due to fertilization is with a dose of 60 t / h / yr.